Posisi Relatif Provinsi di Indonesia Berdasarkan Penggunaan Pengobatan Tradisional: Analisis Komponen Utama Biplot - Lusi Kristiana; Astridya Paramita; Pramita Andarwati; Herti Maryani; nailul izza (Buletin Penelitian Sistem Kesehatan, 2020)
The utilization of traditional health services and the use of traditional medicine in Indonesia is still high. There are socio-cultural-natural resources connection in the use of traditional health services and traditional medicine. This study examines Basic Health Research (Riskesdas) 2018 data relating to Indonesia's top ten provinces' relative position, whose community exercises self-traditional health practices and utilizing traditional health services. The analysis was conducted by using PCA-Biplots. Results showed similarities between North Maluku-Maluku-West Papua; Central Sulawesi-South Sulawesi-East Nusa Tenggara-Papua; Special Region of Yogyakarta-Central Java-East Java; South Kalimantan-Banten, while the others were scattered. The utilization of TOGA had a positive correlation with the utilization of traditional medicines. The result of variable diversity identification showed that the community utilizes traditional health services (83.29%) was higher than community exercising self-traditional health practices (73.19%). Actively monitoring, improving information sharing, and educating people on traditional medicine applications, particularly non-communicable disease issues, should be done according to traditional medicine variables' main characteristics in the region. Traditional medicine should serve promotive and preventive health initiatives, as its efficacy in therapeutic use is still debatable. Abstrak Pemanfaatan pelayanan Kesehatan tradisional (yankestrad) dan penggunaan obat tradisional masih cukup banyak. Terdapat keterkaitan sosial, budaya, dan sumber daya alam dalam pemanfaatan yankestrad dan penggunaan pengobatan tradisional lokal. Penelitian ini menganalisis posisi relatif 10 besar provinsi di Indonesia yang melakukan upaya kestrad sendiri dan memanfaatkan yankestrad berdasarkan data Riskesdas 2018. Analisis posisi relatif dalam artikel ini adalah PCA-Biplot. Hasil analisis menunjukkan pola pengelompokan kemiripan sebagai berikut: Malut-Maluku-Pabar; Sulteng-Sulsel-NTT-Papua; DIY-Jateng-Jatim; Kalsel-Banten, dan lainnya tersebar. Variabel pemanfaatan TOGA, semakin positif variabel, maka diikuti oleh pemanfaatan obat tradisional yang semakin baik. Hasil identifikasi keragaman variabel pada pengelompokan 10 besar provinsi dengan masyarakat memanfaatkan yankestrad (83,29%) mempunyai nilai lebih tinggi daripada masyarakat melakukan upaya kestrad sendiri (73,19%). Pemerintah melalui dinas terkait harus melakukan pemantauan, pemberian informasi dan edukasi pengobatan tradisional khususnya untuk penyakit tidak menular dengan penyesuaian terhadap karakteristik pemanfaatan pengobatan tradisional di wilayah tersebut.